2022
DOI: 10.1111/iep.12436
|View full text |Cite
|
Sign up to set email alerts
|

High level of FHL2 exacerbates the outcome of non‐small cell lung cancer (NSCLC) patients and the malignant phenotype in NSCLC cells

Abstract: Non-small cell lung cancer (NSCLC) is a malignant tumour with high mortality.FHL2 has been identified as a biomarker of lung cancer. This research explored the effects of FHL2 expression on NSCLC. NSCLC-associated data sets were collected from the assistant for clinical bioinformatics and TCGA databases respectively. The association between FHL2 and clinical characteristics, the prognostic significance of FHL2 and the influences of various variables on NSCLC were determined by Pearson's chi-squared test, the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For instance, FHL2 may suppress the growth and differentiation of colorectal cancer cells ( 26 ) but promote cervical cancer cell tumor progression through the regulation of AKT-mTOR pathway ( 27 ). Recently, FHL2 was identified as a biomarker of LUAD that could promote NSCLC progression and migration ( 14 ). Our study reached similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, FHL2 may suppress the growth and differentiation of colorectal cancer cells ( 26 ) but promote cervical cancer cell tumor progression through the regulation of AKT-mTOR pathway ( 27 ). Recently, FHL2 was identified as a biomarker of LUAD that could promote NSCLC progression and migration ( 14 ). Our study reached similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Four-and-a-half LIM-domain protein 2 ( FHL2 ) can directly interact with several proteins and is involved in various biological progress including cell adhesion, proliferation, apoptosis, invasion, and differentiation ( 10 ). It is reported that FHL2 can promote the progression of several cancers, such as ovarian cancer ( 11 ), cervical cancer ( 12 ), esophageal squamous-cell carcinoma ( 13 ), and NSCLC progression ( 14 ). A recent study showed that FHL2 upregulation facilitated the proliferation and migration of NSCLC cells and exacerbated the negative outcomes of patients with NSCLC ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the four diagnostic biomarkers, previous studies showed that FHL2 has been identi ed as a biomarker of lung cancer and high level of FHL2 exacerbates the outcome of patients with non-small cell lung cancer (NSCLC) and the malignant phenotype in NSCLC cells [40]. Among visinin-like proteins (VILIPs), HPCAL1 belongs to the neuronal calcium sensor (NCS) family, which is responsible for calcium signaling in neurons [41].…”
Section: Discussionmentioning
confidence: 99%